Subjects with Knee Osteoarthritis Exhibit Widespread Hyperalgesia to Pressure and Cold - Moss, Penny; Knight, E.; Wright, Tony (PLoS ONE, 2016)
Hyperalgesia to mechanical and thermal stimuli are characteristics of a range of disorders such as tennis elbow, whiplash and fibromyalgia. This study evaluated the presence of local and widespread mechanical and thermal hyperalgesia in individuals with knee osteoarthritis, compared to healthy control subjects. Twenty-three subjects with knee osteoarthritis and 23 healthy controls, matched for age, gender and body mass index, were recruited for the study. Volunteers with any additional chronic pain conditions were excluded. Pain thresholds to pressure, cold and heat were tested at the knee, ipsilateral heel and ipsilateral elbow, in randomized order, using standardised methodology. Significant between-groups differences for pressure pain and cold pain thresholds were found with osteoarthritic subjects demonstrating significantly increased sensitivity to both pressure (p = .018) and cold (p = .003) stimuli, compared with controls. A similar pattern of results extended to the pain-free ipsilateral ankle and elbow indicating widespread pressure and cold hyperalgesia. No significant differences were found between groups for heat pain threshold, although correlations showed that subjects with greater sensitivity to pressure pain were also likely to be more sensitive to both cold pain and heat pain. This study found widespread elevated pain thresholds in subjects with painful knee osteoarthritis, suggesting that altered nociceptive system processing may play a role in ongoing arthritic pain for some patients.